2018
DOI: 10.1002/app.47350
|View full text |Cite
|
Sign up to set email alerts
|

Hot air aging behavior of polypropylene random copolymers

Abstract: This article deals with the global aging behavior of three polypropylene random copolymer (PP-R) materials with varying primary structure and morphology. Hot air aging experiments at elevated temperatures from 95 to 135 C were carried out using micro-sized specimens with a thickness of 100 μm. Technological and analytical aging indicators were monitored for an exposure time of up to 750 days. Independent of comonomer type (ethylene vs. butylene) and morphology (α vs. β crystal form) a critical molar mass of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
2
16
1
Order By: Relevance
“…As expected, the time-to-embrittlement values in hot air were found to strongly depend on the exposure temperature, with time-to-embrittlement values strongly decreasing with increasing temperature. For example, at 95 °C embrittlement times of higher than 15,000 h were determined, while at the highest exposure temperature of 135 °C, total embrittlement was obtained for both grades after about 3300 h. By comparison, the present study revealed time-to-embrittlement values for PP-Rα and PP-Rβ at 60 °C in chlorinated water of 1500 and 2000 h, respectively, both values being significantly below the numbers reported by Grabmann et al [7] for 95 °C and even 135 °C in air. Clearly, hot chlorinated water is a much more aggressive environment than hot air, with polymer degradation occurring even at low temperatures after shorter exposure times.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…As expected, the time-to-embrittlement values in hot air were found to strongly depend on the exposure temperature, with time-to-embrittlement values strongly decreasing with increasing temperature. For example, at 95 °C embrittlement times of higher than 15,000 h were determined, while at the highest exposure temperature of 135 °C, total embrittlement was obtained for both grades after about 3300 h. By comparison, the present study revealed time-to-embrittlement values for PP-Rα and PP-Rβ at 60 °C in chlorinated water of 1500 and 2000 h, respectively, both values being significantly below the numbers reported by Grabmann et al [7] for 95 °C and even 135 °C in air. Clearly, hot chlorinated water is a much more aggressive environment than hot air, with polymer degradation occurring even at low temperatures after shorter exposure times.…”
Section: Discussioncontrasting
confidence: 85%
“…Clearly, hot chlorinated water is a much more aggressive environment than hot air, with polymer degradation occurring even at low temperatures after shorter exposure times. Simultaneously, Grabmann et al [7], as well as this study, revealed PP-Rβ as the material with improved aging resistance. The aggressive nature of chlorine in the liquid environment was also corroborated by the mechanical performance investigations, where PP-Rβ was found to outperform PP-Rα both in terms of tensile behavior after environmental exposure and in fatigue crack growth performance under superimposed mechanical-environmental loading.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In this context, it is important to recognize that the applicability and effectivity of stabilizer systems not only depend on the environmental conditions but also on the molecular and morphological nature of the polymeric base material. Considering this complexity and the necessity for a manageable methodological approach to cover aspects of global and local aging, it is not surprising that only a limited amount of investigations exists on the effects of various stabilizer systems on the global and local aging behavior in polypropylene [4,5,6,7,12,13,14,15,16,17,19,20,39,40,41,42,43]. Nevertheless, regarding the methodological approach, novel test methods have been implemented in the laboratory of the Institute of Polymeric Materials and Testing at the Johannes Kepler University Linz to investigate such phenomena of pure environmental global aging (without stresses) and superimposed mechanical-environmental local aging in an efficient manner [4,5,6,7,12,13,14,15,17,20,40,42].…”
Section: Introductionmentioning
confidence: 99%